Bovine hydroxyapatite (BHA) Strontium Oxide Composites - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2009)
Composites of calcinated bovine bone derived hydroxyapatite (HA) with 5 and 10 wt % SrCO3 were prepared by sintering. The production of HA from natural sources is preferred due to money and time saving reasons. In this study scanning electron microscopy (SEM) investigations and together with measurements of microhardness, density, and compression strength were performed. The experimental results indicated that compression strength and microhardness values of HA-Sr-oxide composites decrease when the content of SrCO3 and sintering temperature increase. The best compression strength values were achieved after sintering at 1000 degrees C. It was seen that at higher temperatures the compression strength and the microhardness values decrease due to the pore formation. The pore formation is very important for scaffold formation for tissue engineering purposes.
Keywords: Hydroxyapatite; Strontium Oxide; Sintering; Microstructure; Mechanical Properties; MECHANICAL-PROPERTIES; CERAMICS